Effect of hysterectomy with opportunistic salpingectomy for uterine fibroids on the development of genitourinary syndrome and ways of its reduction - Proshchenko, Olha; Ventskivska, Iryna (Journal of Education, Health and Sport, 2022)
The article presents the assessment and analysis of the most important predictors and manifestations of genitourinary disorders in women of reproductive age after radical surgical treatment for uterine fibroids in the remote postoperative period. Ways of reducing the severity of symptoms are offered. The aim of the study – to establish the influence of hysterectomy with opportunistic salpingectomy for uterine fibroids on manifestation and progression of genitourinary syndrome and ways of the reduction in its severity. Materials and methods. Comprehensive clinical and laboratory assessment of the impact of hysterectomy with opportunistic salpingectomy for uterine fibroids on the development of metabolic syndrome was conducted at the gynecological department of the “Kyiv Perinatal Center”. The study included 160 women: 90 patients underwent vaginal classical and laporoscopic hysterectomy including fallopian tubes removal; and 70 patients underwent abdominal hysterectomy including fallopian tubes removal. Data on the assessment of pelvic floor condition and urogenital dysfunction were provided using a standardized POP-Q system, both at the stage of preoperative observation and for 1, 3 and 5 years after the surgery. Research results and their discussion. The most important risk factors that allow forming groups of patients requiring individualized approach in the choice of surgical techniques and rehabilitation program were pointed out. The obtained results allowed to isolate UCDT markers in fractions above 20%. 19 women (11.86%) underwent ovarian surgeries and used gonadotropin-releasing hormone agonists. Genitourinary and sexual disorders were diagnosed in 27 cases (19.3%) 12 months after surgery. Vaginoscopy, performed 12 months after surgery, revealed atrophic vaginitis in 58 cases (36.25%) without significant difference in groups. Microscopy of urogenital smears was in norm only in 51 patients (31.86%). Complaints of dysuria were most common among patients (59 – 36.85%). The combination of sexual disorders and other manifestations (flatulence and intestinal discomfort, stool problems, vaginal microbiota disorders, pelvic floor descent, etc.) was revealed in a quarter of women (28 – 17.50%), and more often – after vaginal hysterectomy (17 – 18.89%). Clinical symptoms of urinary incontinence were observed against the background of a negative cough test in almost a third of patients (49 – 30.63%). They were combined with pollakiuria, nocturia, and imperative urgency, exacerbated by alcohol and accompanied by cystalgia and genital prolapse. The use of low doses of estradiol in the rehabilitation program improved the clinical and laboratory parameters of the urogenital tract, reducing the incidence of vulvovaginal atrophy by 13%, normalizing the biocenosis and vaginal pH, reducing clinical manifestations of urinary incontinence (pollakiuria and nocturnal pollakiuria) by 14%, feeling of incomplete bladder emptying – by 15%, stress urinary incontinence – by 16%, vaginal prolapse – by 11%, compared to the group with standard postoperative management, as well as reducing the severity of psycho-emotional and vegetative-vascular manifestations. Conclusion. The expected effect of surgical recovery may be insufficient, and clinical symptoms of genitourinary syndrome may manifest in the postoperative period, which requires the development of clear algorithms for diagnosing urinary incontinence and pelvic floor failure in the preoperative stage and application of long-term preventive measures after hysterectomy in the remote postoperative period. There is no statistically significant difference in the development of genitourinary syndrome with different surgical approaches.